2002
DOI: 10.1200/jco.2002.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical and Pharmacokinetic Study of Pemetrexed and Carboplatin in Patients With Malignant Pleural Mesothelioma

Abstract: The MTD was pemetrexed 500 mg/m(2) and carboplatin AUC 6 mg/mL.min. The recommended phase II dose of the combination is pemetrexed 500 mg/m(2) and carboplatin AUC 5 mg/mL.min. The combination is both active and well tolerated in MPM and deserves further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(72 citation statements)
references
References 37 publications
2
70
0
Order By: Relevance
“…A total of 27 patients were treated with various dose levels of pemetrexed and carboplatin on day 1 of a 21-day schedule (Hughes et al, 2002). In 25 evaluable patients, eight (32%) achieved a partial remmission and 14 experienced stable disease at various dose levels.…”
Section: Antifolatesmentioning
confidence: 99%
“…A total of 27 patients were treated with various dose levels of pemetrexed and carboplatin on day 1 of a 21-day schedule (Hughes et al, 2002). In 25 evaluable patients, eight (32%) achieved a partial remmission and 14 experienced stable disease at various dose levels.…”
Section: Antifolatesmentioning
confidence: 99%
“…In clinical practice, carboplatin is often substituted for cisplatin due to its reduced risk of toxicity (46). Phase II data demonstrated the efficacy of pemetrexed (500 mg/m 2 ) plus carboplatin AUC 5 in MPM (47-49).…”
Section: Combination Of Pemetrexed Added To Platinum Therapymentioning
confidence: 99%
“…Radiation therapy has been shown to alleviate pain in the majority of treated patients, but the duration of symptom control is short lived, hence chemotherapy is generally the treatment of choice. Clinical trials have shown a partial response rate of 32% using a combination of pemetrexed and carboplatin (Hughes et al, 2002). A phase III trial using pemetrexed with cisplatin significantly improved response rates, time to progression, overall survival and quality of life, compared with single agent cisplatin, and suggested that this be used as front-line chemotherapy in MPM patients (Vogelzang et al, 2003).…”
mentioning
confidence: 99%